Comparative analysis of riser base and flowline gas injection on vertical gas-liquid two-phase flow - Brini Ahmed, Salem K.; Aliyu, Aliyu M.; Baba, Yahaya D.; Abdulkadir, Mukhtar; Abdulhadi, Rahil Omar; Lao, Liyun; Yeung, Hoi (MDPI, 2022)
Gas injection is a frequently used method for artificial lift and flow regime rectification in offshore production and transportation flowlines. The flow behaviour in such flowlines is complex and a better understanding of flow characteristics, such as flow patterns, void fraction/hold up distributions and pressure gradient is always required for efficient and optimal design of downstream handling facilities. Injection method and location have been shown to strongly affect downstream fluid behaviour that can have important implications for pumping and downstream facility design, especially if the development length between pipeline and downstream facility is less than L/D = 50 as reported by many investigators. In this article, we provide the results of an experimental investigation into the effects of the gas injection position on the characteristics of the downstream upwards vertical gas flow using a vertical riser with an internal diameter of 52 mm and a length of 10.5 m. A horizontal 40-m-long section connected at the bottom provides options for riser base or horizontal flow line injection of gas. The flowline gas injection is performed 40 m upstream of the riser base. A 16 by 16 capacitance wire mesh sensor and a gamma densitometer were used to measure the gas-liquid phase cross-sectional distribution at the riser top. A detailed analysis of the flow characteristics is carried out based on the measurements. These include flow regimes, cross-sectional liquid holdup distributions and peaking patterns as well as analysis of the time series data. Our findings show that flow behaviours differences due to different gas injection locations were persisting after a development length of 180D in the riser. More specifically, core-peaking liquid holdup occurred at the lower gas injection rates through the flowline, while wall-peaking holdup profiles were established at the same flow conditions for riser base injection. Wall peaking was associated with dispersed bubbly flows and hence non-pulsating as against core-peaking was associated with Taylor bubbles and slug flows. Furthermore, it was found that the riser base injection generally produced lower holdups. It was noted that the circumferential injector used at the riser base promoted high void fraction and hence low liquid holdups. Due to the bubbly flow structure, the slip velocity is smaller than for larger cap bubbles and hence the void fraction is higher. The measurements and observations presented in the paper provides valuable knowledge on riser base/flowline gas introduction that can directly feed into the design of downstream facilities such as storage tanks, slug catchers and separators.
Keywords: two-phase flow; gas injection; vertical pipes; wire mesh sensor; gamma densitometer